LRP8‐mediated selenocysteine uptake is a targetable vulnerability in MYCN‐amplified neuroblastoma - Hamed Alborzinia; Zhiyi Chen; Umut Yildiz; Florencio Porto Freitas; Felix C E Vogel; Julianna Patricia Varga; Jasmin Batani; Christoph Bartenhagen; Werner Schmitz; Gabriele Büchel; Bernhard Michalke; Jashuo Zheng; et al. (EMBO Molecular Medicine)
Abstract Ferroptosis has emerged as an attractive strategy in cancer therapy. Understanding the operational networks regulating ferroptosis may unravel vulnerabilities that could be harnessed for therapeutic benefit. Using CRISPR‐activation screens in ferroptosis hypersensitive cells, we identify the selenoprotein P (SELENOP) receptor, LRP8, as a key determinant protecting MYCN‐amplified neuroblastoma cells from ferroptosis. Genetic deletion of LRP8 leads to ferroptosis as a result of an insufficient supply of selenocysteine, which is required for the translation of the antiferroptotic selenoprotein GPX4. This dependency is caused by low expression of alternative selenium uptake pathways such as system Xc−. The identification of LRP8 as a specific vulnerability of MYCN‐amplified neuroblastoma cells was confirmed in constitutive and inducible LRP8 knockout orthotopic xenografts. These findings disclose a yet‐unaccounted mechanism of selective ferroptosis induction that might be explored as a therapeutic strategy for high‐risk neuroblastoma and potentially other MYCN‐amplified entities.